2019
DOI: 10.29405/solma.v8i1.2996
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Media Pembelajaran SPSS untuk Meningkatkan Kemampuan Statistik Siswa SMK

Abstract: This community service was carried out in the form of a workshop on utilization of SPSS learning media in mathematics learning for vocational high school students in SMK PAB 12 Saentis, Percut Sei Tuan, Deli Serdang, North Sumatera. The target of this service are: 1) to increase students understanding of SPSS learning media in mathematics learning; 2) to improve students' skill in using SPSS learning media; 3) to increase students' knowledge about statistic learning which has an impact of increasing students' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Several previous studies that used Excel and SPSS as learning media to facilitate students in understanding the subject matter concluded that both learning using Excel and SPSS could improve student learning outcomes (Martiningsih ( 2015), (Ramadhani & Sribina (2019), Sundayana (2012), Nurhayati & Novianti (2020), Nurjanah et al (2020), (Tarigan et al, 2020, Jayadi & Anwar (2017), Hasibuan & Hasibuan (2017) and Julaeha (2019)). Other studies that have been conducted also conclude that learning using Excel and SPSS can increase interest (Hasyim & Listiawan, 2014) and can also improve student attitudes towards learning (Nasyaroeka, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies that used Excel and SPSS as learning media to facilitate students in understanding the subject matter concluded that both learning using Excel and SPSS could improve student learning outcomes (Martiningsih ( 2015), (Ramadhani & Sribina (2019), Sundayana (2012), Nurhayati & Novianti (2020), Nurjanah et al (2020), (Tarigan et al, 2020, Jayadi & Anwar (2017), Hasibuan & Hasibuan (2017) and Julaeha (2019)). Other studies that have been conducted also conclude that learning using Excel and SPSS can increase interest (Hasyim & Listiawan, 2014) and can also improve student attitudes towards learning (Nasyaroeka, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…ACCURATE adalah aplikasi yang digunakan untuk memudahkan proses akuntansi (Helmayunita et al, 2019). Dengan aplikasi ACCURATE, maka proses akuntansi hanya sampai tahap penjurnalan saja, sedangkan proses selanjutnya dilakukan oleh sistem (Ramadhani & Sribina, 2019). ACCURATE merupakan perangkat lunak yang dirancang di Indonesia, dan mulai dikenalkan sejak tahun 2000 (Husda et al, 2019).…”
unclassified